Haploid-specific transcription of protamine-myc and protamine-T-antigen fusion genes in transgenic mice. - Stewart, T A (1988)
The protamines are small, basic, arginine-rich proteins synthesized postmeiotically in the testes. Analysis of the regulation of synthesis of the protamine mRNA and protein is restricted by the difficulty in culturing and manipulating the cells in which transcription and translation occur. To avoid these problems, we have produced transgenic mice carrying fusion genes in which sequences 5' to the mouse protamine-2 gene have been linked to exons 2 and 3 of the mouse c-myc gene and, separately, to the simian virus 40 (SV40) early region. We show here that the prot.myc gene is correctly regulated; transcription is detected only in the round spermatids. In one family of transgenic mice carrying the 5' protamine-SV40 T-antigen fusion gene, SV40 early-region mRNA accumulated to the highest level in the testes but was also detected in the thymuses, brains, hearts, and preputial glands of the animals. Although we have demonstrated specific transcription of these fusion genes in the round spermatids, we were not able to detect the SV40 T-antigen protein.